Geochemical measurements from permafrost soils across thaw stages in Peera palsa (Finland) - Baysinger, Mackenzie; Verdonen, Mariana; Kumpula, Timo; Reif, Jakob; Laurent, Mélissa; Liebner, Susanne; Treat, Claire C
This dataset reports measurements from a yearlong laboratory incubation of soils sourced from within the discontinuous permafrost zone in northern Finland. Using an aerial imagery chronosequence documenting the aerial mass loss, we identified four thaw stages and sampled three replicate cores from each thaw stage habitat from our field site (Peera palsa). In September 2022, soil cores were collected from four stages of permafrost thaw habitats with the years since the thaw sequence began: Intact Palsa (2021- Present Day), Intermediate Stage (1997-2012), Recent Thaw Stage (1960-1997), and Outside of 1960 area boundary (1960+). The cores from each thaw stage were taken from surface to depths ranging from 15 to 233.5 cm below surface using an Eijelkamp peat corer for the active layer and a SIPRE (Snow, Ice and Permafrost Research Establishment style corer) for the permafrost soil horizon. The cores were subdivided by soil horizon and then sampled from geochemical data to supplement the incubation gas measurements. One core for each horizon was further subsampled every 10cm for detailed geochemical analysis, and the results from these "long cores" can be seen in the second datasheet. The soil horizons were homogenized within each thaw stage group then incubated anaerobically for 384 days in two temperature treatment groups (4, 20°C) and two experimental treatments in the intact palsa thaw stage (subsets of samples were incubated aerobically, other subsets received an addenda of pond water collected at Peera palsa). Gas production from the sample incubations was measured on a gas chromatograph (7890A, Agilent Technologies, USA) with flame ionization detection (FID) for CO2 and CH4 concentrations. The rate of respiration from the samples were calculated per gram carbon and per gram soil as described in the method of Robertson., et al. (1999) and reported here, along with other relevant parameters.